TRAINING AND ESTABLISHMENT UKS AND IMPLEMENTATION OF PHBS ACTIVITIES AT SDN 14 MANDAU, BENGKALIS - Wahyuni, Islah (JCES (Journal of Character Education Society), 2022)
Abstrak:  Sekolah merupakan lingkungan pendidikan kedua bagi seorang anak dalam mengembangkan dirinya dalam mendapatkan pendidikan dan penanaman perilaku hidup sehat. Melalui Usaha kesehatan Sekolah, kegiatan dokter cilik serta penerapan Perilaku hidup bersih sehat disekolah akan memberikan pengalaman belajar yang sangat penting bagi siswa dalam memahami pentingnnya menjaga pola hidup yang sehat dalam kehidupan sehari-hari. Tujuan kegiatan PKM ini adalah meningkatkan pengetahuan dan keterampilan siswa SD serta membentuk kegiatan UKS, dokter cilik dan bagaimana ber-PHBS ditatanan sekolah. Pelaksanaannya di SDN 14 Mandau duri Bengkalis Riau sebagai bentuk pengabdian dalam kegiatan Merdeka Belajar Kampus Merdeka 2 (MBKM2) oleh dosen Prodi Sarjana Kebidanan dan Profesi Bidan beserta mahasiswa. Teknis pelaksanaannya luring tatap muka dibagi 2 sesi dengan penyampaian materi dan sistem coaching melalui demo praktek serta dilanjutkan online via WhatsApps untuk menindak lanjuti pelaksanaan UKS, dokter cilik dan perubahan perilaku siswa dalam ber-PHBS di sekolah. Keberhasilan kegiatan PKM tampak dari semangat yang ditunjukkan siswa SD dalam mengikuti proses pelatihan ini, dari testimony: siswa merasa sangat tertarik, sadar dan berjanji akan selalu melaksanakan kegiatan UKS dan menerapkan PHBS di sekolah.   Abstract:   School is the second educational environment for a child in developing himself in getting education and inculcating healthy living behavior. Through school health efforts, the activities of little doctors and the application of clean and healthy living behavior in schools will provide a very important learning experience for students in understanding the importance of maintaining a healthy lifestyle in everyday life. The purpose of this PKM activity is to increase the knowledge and skills of elementary school students as well as to form UKS activities, little doctors and how to perform PHBS in school settings. It was held at SDN 14 Mandau thorn Bengkalis Riau as a form of dedication in the Merdeka Learning activities at Merdeka Campus 2 (MBKM2) by lecturers of the Midwifery and Midwifery Profession Study Program and students. The technical implementation is offline face-to-face divided into 2 sessions with the delivery of material and a coaching system through practical demonstrations and continued online via WhatsApps to follow up on the implementation of UKS, little doctors and changes in student behavior in PHBS at school. The success of PKM activities can be seen from the enthusiasm shown by elementary school students in participating in this training process, from testimony: students feel very interested, aware and promise to always carry out UKS activities and implement PHBS in schools.